Article RETRACTED due to malpractice Structured Sprint Training in Physical Education: Effects on Children's Motor Skills and Physical Activity Levels - pardiman (Retos, 2026)
Introduction: Physical activity plays an essential role in children's physical development, particularly in improving motor skills and promoting active lifestyles.Objective: This study aimed to examine the effects of a structured sprint training program on children's motor skills and physical activity levels during physical education classes. Methodology: A quasi-experimental design with a pre-test and post-test control group was employed. A total of 40 elementary school students aged 10–12 years were randomly assigned to an experimental group (n = 20) and a control group (n = 20). Motor skills were assessed using the Test of Gross Motor Development (TGMD-3), and physical activity levels were measured using the Physical Activity Questionnaire for Children (PAQ-C).Results: The results showed significant improvements in the experimental group. Motor skill scores increased from 32.45 ± 4.21 to 41.80 ± 4.73, while the control group improved slightly from 33.10 ± 4.05 to 35.05 ± 4.18. Physical activity levels also increased in the experimental group from 2.71 ± 0.41 to 3.82 ± 0.47, whereas the control group showed a smaller increase from 2.69 ± 0.39 to 2.95 ± 0.42.Discussion: The results suggest that structured sprint training enhances locomotor skills, neuromuscular coordination, and student engagement in physical activity during physical education.Conclusions: Structured sprint training is an effective strategy for improving children's motor skills and increasing physical activity participation in school settings.